Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi di Lingkungan Pemerintahan Kabupaten Kaimana - Lara Carenina Alhamid; Maslichah Maslichah; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the influence of user involvement, personal engineering skills, top management support, training and education programs affecting the performance of accounting information systems partially and simultaneously within the local government of Kaimana regency, West Papua Province. This type of research is correlational research. The data collection technique used is a questionnaire. The data analysis technique used is multiple linear regression analysis with the SPSS 22 program. The results of this study are simultaneous user involvement, personal engineering skills, top management support, training and education programs affecting the performance of accounting information systems in Kaimana Regency. The involvement of users has a significant positive effect on the performance of the accounting information system in Kaimana Regency. Personal engineering skills have a significant positive effect on the performance of the accounting information system in Kaimana Regency. The support of top management has no effect on the performance of the accounting information system in Kaimana County. Training and education programs have a significant positive effect on the performance of accounting information systems in Kaimana Regency. Keywords : Accounting information system performance, user engagement, personal engineering skills, top management support, training and education programs